Palliative Care for Cancer Patients During the COVID-19 Pandemic, With Special Focus on Lung Cancer - Schoenmaekers, Janna J. A. O.; Hendriks, Lizza E. L.; van den Beuken-van Everdingen, Marieke H. J. (Frontiers in Oncology, 2020)
The COVID-19 pandemic caused a massive shift in the distribution of health care. This potentially compromises the (palliative) care for (lung) cancer patients, who are also at high risk for developing COVID-19 related morbidity and mortality. In this opinion article, we will focus on what we have learned from the first wave of COVID-19 and its impact on palliative care for (lung) cancer patients. The implications on the four pillars of palliative care (psychological, social, physical and spiritual) will be discussed. Furthermore, we will provide practical advice on how to maintain and improve palliative care for (lung) cancer patients in case the next pandemic hits.